UNIT 9.25 Molecular Diagnosis of Duchenne Muscular Dystrophy. (1st October 2014) - Nallamilli, Babi Ramesh Reddy; Ankala, Arunkanth; Hegde, Madhuri
Abstract: Duchenne Muscular Dystrophy (DMD) is an X‐linked inherited neuromuscular disorder caused by mutations in the dystrophin gene ( DMD ; locus Xp21.2). The mutation spectrum of DMD is unique in that 65% of causative mutations are intragenic deletions, with intragenic duplications and point mutations (along with other sequence variants) accounting for 6% to 10% and 30% to 35%, respectively. The strategy for molecular diagnostic testing for DMD involves initial screening for deletions/duplications using microarray‐based comparative genomic hybridization (array‐CGH) followed by full‐sequence analysis of DMD for sequence variants. Recently, next‐generation sequencing (NGS)–based targeted gene analysis has become clinically available for detection of point mutations and other sequence variants (small insertions, deletions, and indels). This unit initially discusses the strategic algorithm for establishing a molecular diagnosis of DMD and later provides detailed protocols of current molecular diagnostic methods for DMD, including array‐CGH, PCR‐based Sanger sequencing, and NGS‐based sequencing assay. Curr. Protoc. Hum. Genet . 83:9.25.1‐9.25.29 © 2014 by John Wiley & Sons, Inc.